NATURE+ in Burkina Faso - Report 2023 & Outlook 2024 - Gebrezgabher, Solomie A.; Vinceti, Barbara; Grazioli, Francesca (2023)
The CGIAR Initiative on Nature-Positive Solutions in Burkina Faso works in the provinces of Bazèga, Boulkiemdé, Kadiogo and Oubritenga. Because of the predicted challenges associated with environmental factors such as climate change, soil degradation and rainfall variability, which negatively impact the viability of smallholder agriculture, the transition toward sustainable and resilient agricultural and food systems is paramount. Nature-based solutions can play a major role in this transition.